Pillars of Women in the Scientific Tradition: Tracing the Role of Muslim Scholars in Islamic Education - Binti Nur Afifah (Global Education Journal, 2025)
In South Kalimantan’s interior, a significant shift is unfolding within the realm of Islamic religious instruction, spearheaded by female educators who are redefining conventional theological education. Research examining 25 women religious teachers demonstrates their transformative impact on local communities through progressive leadership methods and contemporary approaches to spiritual teaching. These trailblazing educators have assumed leadership roles within pesantren educational institutions, implementing participatory and welcoming management practices that foster supportive learning spaces for students of all genders. Moving beyond conventional pedagogical frameworks, they have integrated instruction that recognizes gender-specific considerations, particularly focusing on the distinct requirements of women in their communities. They organize substantive conversations covering marriage counseling, healthcare matters, and the interpretation of women’s rights through Islamic jurisprudence, addressing important educational voids. What stands out particularly is their adoption of online technologies to broaden their educational influence. These religious teachers have effectively leveraged social media platforms including YouTube, Instagram, Facebook, and TikTok Live to engage with varied audiences spanning multiple generations. Their technological proficiency enables them to deliver spiritual instruction in modern, relatable formats that appeal to digitally-connected community members. Drawing from comprehensive interview data, field observations, and examination of their digital platform activities, scholars found that these educators are doing more than simply responding to transformation—they are catalyzing it. Their contributions illustrate how Islamic theological education can modernize to address current community requirements while preserving its religious core, establishing that women’s academic leadership plays a vital role in developing accessible, forward-thinking religious educational settings.